2008
DOI: 10.1016/j.biopsych.2007.10.024
|View full text |Cite
|
Sign up to set email alerts
|

The CHRNA5/A3/B4 Gene Cluster Variability as an Important Determinant of Early Alcohol and Tobacco Initiation in Young Adults

Abstract: Background-One potential site of convergence of the nicotine and alcohol actions is the family of the neuronal nicotinic acetylcholine receptors. Our study examines the genetic association between variations in the genomic region containing the CHRNA5, A3 and B4 gene cluster (A5A3B4) and several phenotypes of alcohol and tobacco use in an ethnically diverse young adult sample. Significant results were then replicated in a separate adult population-representative sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
180
2
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(190 citation statements)
references
References 48 publications
3
180
2
5
Order By: Relevance
“…Additional research has demonstrated associations between the CHRNA5-CHRNA3-CHRNB4 gene cluster and smoking initiation (e.g. smoking at least once a month); 1 SNPs in CHRNA5 (rs514743), 1 SNP in CHRNB4 (rs1948), and an intergenic SNP located between CHRNA3 and CHRNB4 (rs8023462) were associated with an earlier age of smoking initiation and were replicated in an independent sample [150].…”
Section: The Chrnb3-chrna6 and Chrna5-chrna3-chrnb4 Gene Clustersmentioning
confidence: 88%
“…Additional research has demonstrated associations between the CHRNA5-CHRNA3-CHRNB4 gene cluster and smoking initiation (e.g. smoking at least once a month); 1 SNPs in CHRNA5 (rs514743), 1 SNP in CHRNB4 (rs1948), and an intergenic SNP located between CHRNA3 and CHRNB4 (rs8023462) were associated with an earlier age of smoking initiation and were replicated in an independent sample [150].…”
Section: The Chrnb3-chrna6 and Chrna5-chrna3-chrnb4 Gene Clustersmentioning
confidence: 88%
“…12,81 Age of SI (and its influence on later life smoking behavior) is another phenotype that has been studied from the genetic perspective (Table 2). 82,83 Development of ND requires exposure to nicotine. Therefore, the most appropriate controls for studying factors that influence severity of ND in smokers are individuals who initiated smoking and had sufficient exposure to develop ND but did not.…”
Section: Genetics Of Nd-related Phenotypesmentioning
confidence: 99%
“…Comorbidity of nicotine and alcohol use is well documented but a common biological mechanism or genetic background has not been shown. 9,83 Association of the CHRNA5-CHRNA3-CHRNB4 locus with alcohol dependence (defined by DSM-IV) was shown for 16 polymorphisms (out of 42 genotyped) in two samples, spanning the CHRNA5-CHRNA3 region and including a SNP (rs588765) that affects mRNA levels. 94 These variants show low LD with most other ND associated SNPs reported earlier.…”
mentioning
confidence: 99%
“…Most prominent among these are the human genetic association studies showing that single nucleotide polymorphisms in the gene cluster CHRNA5/Α3/Β4, encoding for the α3, α5, and β4 nAChR subunits, are closely associated with the risk for heavy smoking, inability to quit, and increased sensitivity to nicotine. [7][8][9][10][11] Further, studies in knockout mice show that the β4 nAChR subunit is necessary for nicotine withdrawal because withdrawal is greatly diminished in β4 null mice, but not in β2 null mice. 12,13 Unlike the wide distribution of α4β2 nAChR in the brain, the α3 and β4 subunits are expressed in a restricted number of brain areas, mainly the medial habenula and interpeduncular nucleus, major cholinergic tracts in the brain that have recently garnered increasing attention for their involvement in various aspects of nicotine dependence.…”
Section: Introductionmentioning
confidence: 99%